NASAL LEECH- A RARE CAUSE OF SEVERE ANEMIA - Siddiqui, Tahir Saeed; Qureshi, Ihsan; Mufti, Tariq Saeed (Journal of Ayub Medical College Abbottabad, 2005)
Spontaneous epistaxis, nasal trauma and foreign bodies are common causes of nasal bleed in children. Epistaxis and haematemesis due to leeches have been reported in literature. Here we present a rare case of severe anemia caused by a single leech infestation of nasal cavity that required blood transfusion. Keywords: Nose, Anemia, Leech